On effect of almond skin powder waste reinforcement in PA6: Rheological, thermal and wear properties. (2020) - Mankotia, Karan; Singh, Ishbir; Singh, Rupinder
Abstract: The use of almond skin powder (ASP) as reinforcement in different thermoplastics has been widely explored for improving mechanical properties. But hitherto little has been reported on ASP reinforcement in polyamide6 (PA6) for establishing rheological, thermal (heat capacity) and wear properties in 3D printing applications. This paper reports the effect of ASP reinforcement in PA6 on rheological, thermal and wear properties for possible 3D printing by using commercial fused deposition modelling (FDM). The results of study suggests that with increase in ASP reinforcement (0–7.5 wt% the melt flow index (MFI) increases from 17.27 g/10 min to 26.23 g/10 min but as ASP wt% increases to 10% in PA6, the reduction in MFI (19 g/10 min) was observed. As regards to thermal stability was concerned it has been ascertained that with increase of ASP reinforcement in PA6, the heat capacity significantly reduces (with addition of ASP in PA6 0–10 wt% from 43.75j/g to 22.16j/g) based upon differential scanning calorimeter (DSC) analysis. Further based upon pin on disk test (under dry sliding conditions) the significant decrease in wear rate was noticed (453–200 µm) with addition of ASP in PA6. The results are supported with optical photo-micrographic analysis (for surface properties).